Is syllable segmentation developmentally constrained by consonant sonority within syllable boundaries in silent reading? Evidence in French children. (16th December 2014) - Maïonchi‐Pino, Norbert; de Cara, Bruno; Écalle, Jean; Magnan, Annie
<x xml:space="preserve">Abstract</x> There is agreement that French typically reading children use syllable‐sized units to segment words. Although the statistical properties of the initial syllables or the clusters within syllable boundaries seem to be crucial for syllable segmentation, little is known about the role of consonant sonority in silent reading. In two experiments that used audio‐visual and visual pseudoword recognition tasks with 300 French typically developing children, we showed a progressive increase in the use of syllable segmentation from the first through fifth years of reading instruction. The children were influenced both by an optimal 'sonorant coda–obstruent onset' sonority profile and by the individual position‐dependent consonant sonority within syllable boundaries. Orthographic and phonological statistical properties did not clearly modulate the response patterns. We provide innovative data to help further understand the developmental course of the use of syllable segmentation as determined by sonority. We discuss our results in the light of linguistic principles.